On the optimal progressivity of the income tax code - Juan Carlos Conesa; Dirk Krueger (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
This paper computes the optimal progressivity of the income tax code in a dynamic general equilibrium model with household heterogeneity in which uninsurable labor productivity risk gives rise to a nontrivial income and wealth distribution. A progressive tax system serves as a partial substitute for missing insurance markets and enhances an equal distribution of economic welfare. These beneficial effects of a progressive tax system have to be traded off against the efficiency loss arising from distorting endogenous labor supply and capital accumulation decisions. Using a utilitarian steady state social welfare criterion we find that the optimal US income tax is well approximated by a flat tax rate of 17:2% and a fixed deduction of about 9,400. The steady state welfare gains from a fundamental tax reform towards this tax system are equivalent to 1:7% higher consumption in each state of the world. An explicit computation of the transition path induced by a reform of the current towards the optimal tax system indicates that a majority of the population currently alive (roughly 62%) would experience welfare gains, suggesting that such fundamental income tax reform is not only desirable, but may also be politically feasible.
urn:nbn:de:hebis:30-10855
Keywords: E62; H21; H24; 330; Progressive Taxation; Optimal Taxation; Flat Taxes; Social Insurance; Transition; Steuerprogression; Einkommensteuer; Optimale Besteuerung; Sozialversicherung; Allgemeines Gleichgewicht; USA